Clinical performance of the fully automated Lumipulse plasma p‐tau217 assay in mild cognitive impairment and mild dementia - Adam H. Dyer; Jean Dunne; Helena Dolphin; Laura Morrison; Antoinette O'Connor; Sarah Fullam; Tara Kenny; Aoife Fallon; Sean O'Dowd; Nollaig M. Bourke; Niall P. Conlon; Sean P. Kennelly; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Introduction Plasma phosphorylated tau (p‐tau)217 is a leading blood‐biomarker for the detection of amyloid beta (Aβ) pathology. We assessed the performance of a fully automated plasma p‐tau217 immunoassay to detect Aβ pathology in mild cognitive impairment (MCI)/mild dementia. Methods Paired plasma and cerebrospinal fluid (CSF) samples were obtained at time of diagnostic lumbar puncture (LP) in a specialist memory service. Plasma p‐tau217 was measured using the Lumipulse immunoassay platform and ability to detect CSF‐defined Aβ positivity assessed. Results Of 148 participants (69.4 ± 6.5 years; 54.1% female), 101 had MCI and 47 mild dementia. Median plasma p‐tau217 was > 4‐fold higher in Aβ+ vs Aβ− individuals with an area under the curve of 0.92 (0.87–0.97). Application of 90%, 95%, and 97.5% sensitivity/specificity thresholds for plasma p‐tau217 may have obviated the need for more than half of LPs. Discussion Our real‐world data support the clinical use of fully automated plasma p‐tau217 immunoassays, although further studies in more diverse cohorts are required. HIGHLIGHTS Plasma phosphorylated tau (p‐tau)217 was measured using a fully automated immunoassay (Lumipulse). P‐tau217 was > 4‐fold higher in amyloid beta (Aβ)+ versus Aβ− individuals. Plasma p‐tau217 had an area under the curve of 0.92 for detection of Aβ status. Using a previously proposed two‐threshold approach may avoid more than half of lumbar punctures.